Transformation of Islamic Studies in The Digital Era: Opportunities and Challenges - Ari Prima; Julhadi Julhadi; Mursal Mursal (Yayasan Adra Karima Hubbi, 2024)
The transformation of Islamic studies in the digital era has brought significant impacts on research methodologies, accessibility to knowledge sources, and challenges related to scholarly authority. The digitization of Islamic literature has enabled broader access to Islamic sources, but it has also raised challenges concerning the validity and authority of these sources. Technologies such as big data and artificial intelligence (AI) have opened new opportunities for Islamic studies to become more empirical. However, the use of these methods also faces potential biases and data manipulation. Additionally, the phenomenon of